Prospective study of the prescribing pattern of antibiotics and their outcome in patients admitted to intensive care unit at tertiary center - H. G., Pavithra; Ahmed, Syed Mohsin; H. A., Krishnamurthy (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Antibiotics are currently the most commonly prescribed drugs in hospitals, worldwide. overuse of antibiotics has important economic implications. Periodic evaluation of drug utilization in the intensive care unit (ICU) is necessary for optimization of health care system, proper use of resources and making prescription policy because ICU is considered as the epi-center of antimicrobial resistance. The aim of this study is to evaluate antibiotic prescription and consumption patterns at admission into intensive care unit and to know the average costs of antibiotics. Methods: The prescription data on 250 consecutive patients at admission into the ICU was audited from January to March 2019. Total antibiotics, dose, route and cost of antibiotics were noted and the defined daily dose/100 bed days of most common antibiotics were calculated. Statistical analysis is done using SPSS software. Results: A total of 689 antibiotics were prescribed in the 250 patients studied that is, an average of 2.28 antibiotics/prescription. Empirical antibiotics were prescribed to all the patients admitted to ICU. Average cost of the antibiotics was rupees 163.89 per patients. The most commonly prescribed antibiotic at ICU admission was ceftriaxone (62%) of all prescription. Second most common is metronidazole (32%). In this study, 76 patients recovered while 174 patients expired. Conclusions: Our study reveals that antibiotics are widely prescribed in critically ill patients and form significant drug consumed in the ICU. At admission elderly patients are prescribed >2 antibiotics and prescribing antibiotics where the cost of antibiotic is high.